The Influence of the Implementation of Local Government Information Systems, Human Resources, and Internal Control on the Qualitative Characteristics of Jambi City Government Financial Reports - Siregar, Ermina; Sam, Iskandar; Tiswiyanti, Wiwik (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of the application of the Regional Government Information System (SIPD), the quality of human resources (HR), and internal control on the qualitative characteristics of the financial statements of the Jambi City Government. The quality of local government financial reports is an important indicator in assessing the accountability and transparency of public financial management. By utilizing data from the Jambi City Government, this study uses a quantitative method with a survey approach to test the proposed hypothesis. The results showed that the implementation of SIPD, the quality of human resources, and internal control significantly positively affected the qualitative characteristics of financial statements, which include relevance, reliability, comparability, and understandability. This study provides practical implications for local governments in improving the quality of financial statements through optimizing information systems, developing human resource competencies, and strengthening internal control systems.